2002
DOI: 10.1287/moor.27.4.775.295
|View full text |Cite
|
Sign up to set email alerts
|

The Zero Duality Gap Property and Lower Semicontinuity of the Perturbation Function

Abstract: We examine the validity of the zero duality gap properties for two important dual schemes: a generalized augmented Lagrangian dual scheme and a nonlinear Lagrange-type dual scheme. The necessary and sufficient conditions for the zero duality gap property to hold are established in terms of the lower semicontinuity of the perturbation functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…because (19) shows that the infimum value q k j (λ 2 ) cannot be attained over the set X(r 0 ) . The above expression contradicts (14), and hence asymptotic duality holds.…”
Section: C108mentioning
confidence: 99%
See 1 more Smart Citation
“…because (19) shows that the infimum value q k j (λ 2 ) cannot be attained over the set X(r 0 ) . The above expression contradicts (14), and hence asymptotic duality holds.…”
Section: C108mentioning
confidence: 99%
“…Indeed, it has been shown that for a certain family of augmented Lagrangians, both zero duality gap and saddle point properties hold [18,Chapter 11]. These duality properties have been extended to more general kinds of Lagrangians and more general frameworks (including infinite dimensional spaces) [11,13,17,19,20]. Many solution techniques for nonconvex optimization rely on the good duality properties of augmented Lagrangians [2,3,4,5,6,7,8,9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Augmented Lagrangians with a nonconvex augmenting function have been intensively studied as well (see [9,17,8,19,6,23,24,25] and references therein). Some of these references (e.g., [9,17,6,19]) use abstract convexity tools in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these references (e.g., [9,17,6,19]) use abstract convexity tools in their analysis. Our aim is: (i) to present a unified analysis for the examination of nonconvex augmented Lagrangians for a wider family of augmenting terms, and (ii) express the main definitions and facts describing the augmented Lagrangian theory in terms of abstract convexity tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation